Effectiveness of Management Accounting Systems for Cashier Management Hr. Ambar Batik Klaten: - sari, Yane Puspito (PT FORMOSA CENDEKIA GLOBAL, 2024)
With increasingly advanced technology, it will make it easier for us to do our work. Supported by increasingly sophisticated technological facilities, we increasingly need this technology to lighten our workload. The global crisis that occurred recently is a lesson for us to be smarter in developing the businesses we have. With increasingly developing technology, we can make it the right solution for the development of our business. With the increasingly advanced development of information technology, information systems can be used as an innovation for business development. HR. Ambar Batik uses this system to face the global competition that occurs today. Entrepreneurs are required to be smarter in carrying out new innovations to advance their business. Apart from batik designs being used as better innovations, better information systems are also capable of enabling business development. The data collected in this research includes data about Craftsmen HR. Ambar Batik, Bayat, Wedi, Klaten, Central Java, and the information system used at Ambar Batik. Data collection techniques were carried out by means of observation, interviews, documentation and literature.